2016
DOI: 10.1007/s00251-016-0903-4
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and distribution of FCN2 and FCN3 functional variants among MBL2 genotypes

Abstract: The six types of pattern recognition molecules (PRMs) that initiate complement via the lectin pathway (LP) comprise collectins and ficolins. The importance of having various PRMs to initiate the LP is currently unclear. Mannan-binding lectin (MBL) is a collectin member of the LP PRMs. MBL deficiency is common with mild clinical consequence. Thus, the lack of MBL may be compensated for by the other PRMs. We hypothesized that variants FCN2 + 6424 and FCN3 + 1637delC that cause gene-dose-dependent reduction in fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 88 publications
3
17
0
3
Order By: Relevance
“…For instance, when the level of MBL is low, the level of L-ficolin, H-ficolin or both was high, and this may be due to the necessity of compensation within the lectin pathway. It has been reported that when MBL deficient the level of L-ficolin increased [40] due to the genetic balance and importance of the reparation in the immune system [41].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, when the level of MBL is low, the level of L-ficolin, H-ficolin or both was high, and this may be due to the necessity of compensation within the lectin pathway. It has been reported that when MBL deficient the level of L-ficolin increased [40] due to the genetic balance and importance of the reparation in the immune system [41].…”
Section: Discussionmentioning
confidence: 99%
“…Due to its rarity, it is still unclear whether it is a lifethreatening condition with variable penetrance or acts as a disease modifier [89]. Partial ficolin-2 (or L-ficolin) and ficolin-3 (or H-ficolin) insufficiencies are not well studied and are of uncertain clinical significance [90,91].…”
Section: Lectinmentioning
confidence: 99%
“…Malpuech, Michels and Mingarelli-Carnevale (3MC) syndrome is characterized by facial dysmorphia and other developmental defects such as cleft lip and palate, postnatal growth deficiency, cognitive impairment and hearing loss [13,90,91,103]. It is caused by homozygous mutations in the MASP1 gene (3MC syndrome 1) or members of the collectin subfamily COLEC10 or COLEC11 (3MC syndrome 2) [103].…”
Section: Masp1mentioning
confidence: 99%
“…Homozygosity for +1637delC happens very rarely (1-2 %): only 6 cases have been described in the literature available (all of them suffered from severe infections in early childhood). Data on the population frequency of heterozygous carriage are also scarce, i. e. 15 heterozygotes out of 483 examined individuals were identified in the Icelandic cohort of healthy donors (the frequency was 1.5 %) (Bjarnadottir et al, 2016).…”
Section: Introductionmentioning
confidence: 99%